Comparison of the systemic and pulmonary inflammatory response to endotoxin of neutropenic and non-neutropenic rats - Heidemann Sabrina M; Glibetic Maria (BMC, 2007)
Abstract Background Neutrophil infiltration commonly occurs in acute lung injury and may be partly responsible for the inflammatory response. However, acute lung injury still occurs in the neutropenic host. The objectives of this study are to determine if inflammation and acute lung injury are worse in neutropenic versus the normal host after endotoxemia. Methods Rats were divided into four groups: 1) control, 2) neutropenic, 3) endotoxemic and 4) endotoxemic and neutropenic. Tumor necrosis factor (TNF)-α and macrophage inflammatory protein (MIP-2) were measured in the blood, lung lavage and for mRNA in the lung. Arterial blood gases were measured to determine the alveolar-arterial oxygen gradient which reflects on lung injury. Results In endotoxemia, the neutropenic rats had lower plasma TNF-α (116 ± 73 vs. 202 ± 31 pg/ml) and higher plasma MIP-2 (26.8 + 11.9 vs. 15.6 + 6.9 ng/ml) when compared to non-neutropenic rats. The endotoxemic, neutropenic rats had worse lung injury than the endotoxemic, non-neutropenic rats as shown by increase in the alveolar-arterial oxygen gradient (24 ± 5 vs. 12 ± 9 torr). However, lavage concentrations of TNF-α and MIP-2 were similar in both groups. Conclusion Neutrophils may regulate TNF-α and MIP-2 production in endotoxemia. The elevation in plasma MIP-2 in the endotoxemic, neutropenic rat may be secondary to the lack of a neutrophil response to inhibit production or release of MIP-2. In endotoxemia, the severe lung injury observed in neutropenic rats does not depend on TNF-α or MIP-2 produced in the lung.